Polymer Composites in Present Scenario - Chandra, Sarita; Uniyal, Divya; Gill, Fateh Singh (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*289.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.909627);" role="presentation">Present scenario of growing development demands more sophisticated and engineered materials to facilitate the <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*302.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927373);" role="presentation">lifestyle and to meet the challenges in the establishment of colonies in space. The advancements in composite <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*315.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.945195);" role="presentation">technology meet the growing demands. <span dir="ltr" style="left: calc(var(–scale-factor)*240.89px); top: calc(var(–scale-factor)*315.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.954908);" role="presentation">Composites are the engineered material for future. There are many <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*329.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.906475);" role="presentation">scopes in composites with various emerging nanotechnology and smart materials. <span dir="ltr" style="left: calc(var(–scale-factor)*402.31px); top: calc(var(–scale-factor)*329.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93009);" role="presentation">This paper is a brief review of <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*342.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.903058);" role="presentation">the composite’s concept and their <span dir="ltr" style="left: calc(var(–scale-factor)*208.73px); top: calc(var(–scale-factor)*342.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.901561);" role="presentation">types. The <span dir="ltr" style="left: calc(var(–scale-factor)*253.49px); top: calc(var(–scale-factor)*342.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.957917);" role="presentation">differentiation <span dir="ltr" style="left: calc(var(–scale-factor)*313.51px); top: calc(var(–scale-factor)*342.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.8836);" role="presentation">between <span dir="ltr" style="left: calc(var(–scale-factor)*349.51px); top: calc(var(–scale-factor)*342.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.897881);" role="presentation">the elect<span dir="ltr" style="left: calc(var(–scale-factor)*383.35px); top: calc(var(–scale-factor)*342.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931813);" role="presentation">ronically conducting polymers and <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*355.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.914267);" role="presentation">conducting polymer composites <span dir="ltr" style="left: calc(var(–scale-factor)*202.25px); top: calc(var(–scale-factor)*355.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.847983);" role="presentation">are <span dir="ltr" style="left: calc(var(–scale-factor)*217.01px); top: calc(var(–scale-factor)*355.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.878246);" role="presentation">also <span dir="ltr" style="left: calc(var(–scale-factor)*235.61px); top: calc(var(–scale-factor)*355.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.86242);" role="presentation">discussed <span dir="ltr" style="left: calc(var(–scale-factor)*276.41px); top: calc(var(–scale-factor)*355.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.928624);" role="presentation">along with their contemporary <span dir="ltr" style="left: calc(var(–scale-factor)*400.27px); top: calc(var(–scale-factor)*355.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919312);" role="presentation">applications.